GAME INTERAKTIF BERBASIS UNIVERSAL DESIGN LEARNING BAGI SISWA SLOW LEARNER DI SEKOLAH INKLUSI - Putri Zachrotul Chumairo; Mohammad Efendi; Ahmad Samawi; Diniy Hidayaturrahman; Ediyanto Ediyanto; Asep Sunandar (Jurnal Pendidikan (Teori dan Praktik), 2021)
Slow learning is a learning disability in children that greatly slows down the learning process so that every learning activity takes longer than their peers. Universal Design for Learning (UDL) is a learning design defined as the design of material that is generally made to be more easily understood by diverse students in an inclusive classroom. That way, UDL aims to minimize learning difficulties for students with different learning needs, including students with special needs. In learning, media is an important factor that helps support learning success, especially for students with special needs, including children who are slow to learn. Learning media that are considered suitable to support the success of children slow to learn are interactive games whose core material is presented in the form of videos that are enhanced with audio and visual media. Audio media with narrated and text, graphics, images, visual animations, and interesting kinesthetic interactions to sharpen students' abilities. The method used to create this article is literature review from various relevant sources. The result of this study is that the use of interactive game learning media based on Universal Design Learning (UDL) can help provide convenience for slow learner students in understanding the subject matter at school.